Islam : What Non-Muslims Should Know - Kaltner, John, 1954- (Book collections on Project MUSE., 2016)
Recent events have focused attention on Islam, the often- misunderstood faith of one billion people. Westerners are showing a new curiosity about Islam and other religions, in part, perhaps, because religion is arguably the single most important and volatile factor in geopolitics today. Islam needs to be understood on its own terms, apart from extreme expressions, John Kaltner argues. This revised and expanded edition of a trusted text offers updated information about Islam in an accessible and sympathetic presentation. Kaltner presents Islam as first and foremost a religion of practices. Showing the deep humanism of Islam and its most cherished commitments, Kaltner presents Islam through assertions that counter frequent misconceptions of the faith.